Penerapan Model Self-Directed Learning Dalam Peningkatan Hasil Belajar Pendidikan Jasmani di Sekolah Menegah Pertama Cahaya Pengharapan Abadi - Aser Paul Nainggolan; Rizki Bastanta B Manalu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to improve student learning outcomes by utilizing the self-directed learning. learning model. CAR (classroom action research) was used as the research design, and was conducted on 31 seventh grade students at Cahaya Pengharapan Abadi Junior High School. This CAR cycle is planning, implementation, observation, and reflection. Observations, questionnaires, field notes, tests, and documentation were used as data collection tools. The material is a big ball game. The results showed that this class action can be concluded that the teacher and student activities reflect the Self-Directed Learning learning model, the teacher's ability to manage learning increased from 3.32 to 3.83, and individual completeness increased from 75.52% (good) in the cycle. I became 87.10% (very good) in the second cycle. Classical completeness increased from 70% (good) in the first cycle to 82% (very good) in the second cycle, and the use of the Self-Directed Learning learning model in learning received a good reaction, with 89 percent of students feeling involved and beneficial.